Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V SDN Sei Pimping - Evi Hafizaturrahmi; Sunarno (CV. ITTC INDONESIA, 2024)
The problem in this study is that when learning Mathematics material on fraction calculation operations students tend to be passive and do not want to ask questions and when the teacher asks questions to students, they only answer these questions with answers that are already listed in the book. To follow up on these problems, the researchers tried to provide problem solving, namely by using the inquiry model. The approach used in this research is qualitative research and this type of research applies classroom action research. The types of data presented in this study are qualitative data and quantitative data. Qualitative data in the form of data on teacher activities and student activities in the teaching and learning process activities, through observations with observation sheets. Quantitative data in the form of student learning outcomes obtained through written tests at the end of each meeting. This research was conducted at SDN Sei Pimping Tabalong Regency in class V in the 2022/2023 academic year. After conducting 4 meetings, the results showed that the activities of teachers, students and learning outcomes increased at each meeting with the categories